2016
DOI: 10.5858/arpa.2016-0108-ra
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Workflows and Processing of Cytologic Samples for Comprehensive Analysis by Next-Generation Sequencing: Memorial Sloan Kettering Cancer Center Experience

Abstract: The value and suitability of cytology specimens for molecular diagnosis has been demonstrated by numerous studies. In practice, however, the success rates vary widely across institutions depending on the disease setting, institutional practices of acquisition, handling/processing, and testing methodologies. As the number of clinically relevant biomarkers continues to increase, more laboratories are turning to next-generation sequencing platforms for testing. Although amplicon-based next-generation sequencing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 33 publications
1
86
0
Order By: Relevance
“…Liquid cytology samples, including FNA rinse material, have been demonstrated to be adequate for genomic testing in institutions that have validated these types of samples . In a prior study from our institution, adequate material was obtained for genomic testing from residual FNA rinse or FNA‐acquired body fluid specimens in all 17 cases when tumor cellularity was ≥ 10% in the aspirate .…”
Section: Discussionmentioning
confidence: 99%
“…Liquid cytology samples, including FNA rinse material, have been demonstrated to be adequate for genomic testing in institutions that have validated these types of samples . In a prior study from our institution, adequate material was obtained for genomic testing from residual FNA rinse or FNA‐acquired body fluid specimens in all 17 cases when tumor cellularity was ≥ 10% in the aspirate .…”
Section: Discussionmentioning
confidence: 99%
“…Given the diversity of cytopathologic specimen types and the different methods of fixation and processing available, options for procuring DNA from cytologic specimens for molecular analysis vary; material can be successfully obtained from cell blocks, smears, cytospins, and liquid-based preparations. 7,9,11,12,14,[19][20][21][22][23][24][25] Most commonly, cell blocks are used for molecular testing on cytopathologic specimens. 21 The cell block closely approximates surgical pathology material; tissue fragments from cytopathologic specimens are embedded in paraffin and are sectioned akin to surgical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…29 Although liquid-based cytology specimens are not commonly used for molecular testing of lung adenocarcinomas, 21 a few groups have reported their utility. 7,12,14,25 In our laboratory, we have found that the liquid-based cytology specimen is an excellent resource for EGFR mutation analysis and ALK FISH. We have implemented this method of molecular testing for all of our liquid-based cytology specimen types, including EBUS-TBNA, computed tomography-guided transthoracic fine-needle aspiration, peripheral fine-needle aspiration, and effusion cytology specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…moderate-to-high tumor content (all from Group B) on smears/TP, which if triaged differently, would have theoretically resulted in greater cellularity of cell blocks and improved the overall results of Group B.Specific components of triage are often overlooked and underaddressed with limited reports calling attention to proper specimen acquisition, triage, and management 12,36. These are significant elements of ROSE that could increase MT adequacy 37. Having >1 person (e.g., Group A) from cytology participate in ROSE at start of procedure was advantageous for a few reasons.…”
mentioning
confidence: 99%